Alcohol use among women attending antenatal care in Buffalo City, Eastern Cape - Bredenkamp, Petrus Johannes (Rhodes University, Faculty of Humanities, Department of Psychology)
Alcohol use during pregnancy is known to cause neurodevelopmental disorders in offspring, known as Fetal Alcohol Spectrum Disorders (FASD). High prevalence of FASD has been observed in certain parts South Africa, but many areas of the country remain unstudied, and factors contributing to drinking among pregnant women are poorly understood. This study surveyed 1099 women attending antenatal care at public primary healthcare facilities in the Buffalo City Metropolitan Area in the Eastern Cape. Data was collected using the Alcohol Use Identification Test, a 10-item self-report measure of drinking behaviour in isiXhosa, English, and Afrikaans. Factors associated with alcohol use, risky drinking, binge drinking, and hazardous/harmful drinking were identified using logistic regression. A minority of the sample reported alcohol use (64%). Among those reporting alcohol use, most reported occasional binge drinking (63%) and met criteria for risky drinking (59%) and hazardous/harmful drinking (52%). Living with a regular drinker was significantly associated with alcohol use (OR 1.98, 95% CI 1.51 "“ 2.58), risky drinking (OR 2.03, 95% CI 1.49 "“ 2.76), binge drinking (OR 2.21, 95% CI 1.64 "“ 2.97), and hazardous/harmful drinking (OR 2.0, 95% CI 1.41 "“ 2.99). However, women who were married/cohabiting were less likely to report alcohol use (OR .71, 95% CI .53 - .95). Experiencing intimate partner violence during the current pregnancy was associated with alcohol use (OR 2.42, 95% CI 1.38 "“ 4.27) and hazardous/harmful drinking (OR 2.62, 95% CI 1.32 "“ 5.22). In this study, women who identified as Coloured were more likely to report alcohol use than Women who identified as African (OR 2.74, 95% CI 1.4 "“ 5.36). These findings simultaneously provide evidence of problematic drinking among pregnant women in a previously understudied area and show that external factors affect women's drinking behaviour during pregnancy. Interventions aimed at reducing the incidence of FASD should consider alcohol use by pregnant women in the context of their lived experiences.
Keywords: Alcoholism in pregnancy -- South Africa Buffalo City; Fetal alcohol spectrum disorders; Prenatal care -- South Africa Buffalo City; Alcoholism Social aspects -- South Africa Buffalo City